2010
DOI: 10.1152/japplphysiol.00150.2010
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced intrapulmonary arteriovenous shunting at rest in healthy humans

Abstract: Intrapulmonary arteriovenous (IPAV) shunting has been shown to occur at rest in some subjects breathing a hypoxic gas mixture [fraction of inspired oxygen (FI(O(2))) = 0.12] for brief periods of time. In the present study we set out to determine if IPAV shunting could be induced at rest in all subjects exposed to hypoxia for 30 min. Twelve subjects (6 women) breathed four levels of hypoxia (FI(O(2)) = 0.16, 0.14, 0.12, and 0.10) for 30 min each in either an ascending or descending order with a 15-min normoxic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
143
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(156 citation statements)
references
References 44 publications
(61 reference statements)
12
143
1
Order By: Relevance
“…25 It has been reported that intrapulmonary shunt varies by the fraction of inspired O2 and that hypoxic conditions increase intrapulmonary shunt. 26 To minimize the influence of variation in SaO2 on intrapulmonary shunt, we used intrapulmonary shunt during O2 administration for the analyses. After administration of O2, we performed blood gas analyses again to obtain intrapulmonary shunt, which was calculated with the following formula: 25…”
Section: Respiratory Function Testsmentioning
confidence: 99%
“…25 It has been reported that intrapulmonary shunt varies by the fraction of inspired O2 and that hypoxic conditions increase intrapulmonary shunt. 26 To minimize the influence of variation in SaO2 on intrapulmonary shunt, we used intrapulmonary shunt during O2 administration for the analyses. After administration of O2, we performed blood gas analyses again to obtain intrapulmonary shunt, which was calculated with the following formula: 25…”
Section: Respiratory Function Testsmentioning
confidence: 99%
“…We and others have documented the presence of transiently recruitable IPAVs in ∼90% of healthy humans. [2][3][4]8,9,[29][30] Although the size of IPAVs has never been directly determined in humans under physiologic conditions, data from isolated lung and intact animal studies suggest that these pathways are large (.200 mm) and are located early in the pulmonary vascular tree. 1,[31][32][33] Why Is This Case Relevant to the Clinician?…”
Section: Discussionmentioning
confidence: 99%
“…Laurie et al demonstrated that both the level of hypoxia and the duration of the exposure influence IPAVs such that a mild hypoxic stimulus can be effective if it is prolonged. 30 Similarly, exposure to adrenergic stimuli may overcome the effects of hyperoxia if the dosing is prolonged. It is possible that if they had prolonged the infusion of epinephrine, they would also have observed IPAV recruitment despite the 100% O 2 breathing.…”
Section: What Does This Case Teach Us About Ipav Regulation?mentioning
confidence: 99%
“…Typically, 0.5-1 ml of air and 4-10 ml of saline are used to manually agitate between two syringes connected by stopcocks for a total injection volume of 10 ml (Otto, 2004;Feigenbaum, 2005;Woods et al, 2010). In a research setting, equal success has been achieved in detecting right-to-left shunts via intrapulmonary arteriovenous anastomoses using 0.5-1 ml of air and 3-5 ml of saline, for a total injection volume of 5 ml (Stickland & Lovering, 2006;Laurie et al, 2010;Lovering et al, 2010;Elliott et al, 2011a). The agitated saline mix solution should be injected as a bolus, forcibly by hand.…”
Section: Equipment Instrumentation and Techniquementioning
confidence: 99%
“…There are numerous scoring methods used in both clinical and research settings for semiquantification of right-to-left shunt with saline contrast bubbles (Barzilai et al, 1991;Lovering et al, 2008b;La Gerche et al, 2010;Laurie et al, 2010). These scoring methods take into account the density and spatial distribution of saline contrast bubbles in the left heart.…”
Section: Semi-quantification Of Right-to-left Shuntmentioning
confidence: 99%